A new epidescemetic keratoprosthesis: pilot investigation and proof of concept of a new alternative solution for corneal blindness. Issue 11 (13th April 2015) - Alio, Jorge L; Abdelghany, Ahmed A; Abu-Mustafa, Sabat K; Zein, G
Abstract : Purpose: To report the outcomes of a new model of epidescemetic keratoprosthesis (Kpro) implanted without total corneal trephination. Methods: Patients were considered for implantation with the new Kpro model (KeraKlear) if they were at high risk of failure with standard penetrating keratoplasty (PK) or showed conditions with a poor prognosis following PK such as severe chemical injury. We used femtosecond laser to create the surgical planes adequate for the purpose of the Kpro implantation, and the Kpro was implanted intralamellar in 11 eyes and epidescemetical in 4 eyes. Follow-up was between 7 and 21 months and mainly for anatomical outcomes and complications. Results: For the intralamellar technique, the anatomical outcome was excellent in five eyes with no complications. The other six eyes developed complications such as deep corneal inflammatory membrane, totally vascularised cornea, extrusion of the Kpro and corneal melting, all of which were managed successfully. No eye was lost. For the epidescemetical technique, the anatomical outcome was excellent in all four eyes. Conclusions: The new KeraKlear Kpro has proved to be a viable alternative to corneal transplantation with potential advantages like decreased risk of endophthalmitis, expulsive haemorrhage and worsening glaucoma. KeraKlear Kpro is better tolerated and less prone to complications when implanted epidescemetically; cases with poor corneal quality are better associated to a lamellar fenestrated donor corneal graft, leaving the posterior corneal surface intact and implanting the Kpro between.